2019
DOI: 10.3390/toxins11020118
|View full text |Cite|
|
Sign up to set email alerts
|

NaCl Inhibits Citrinin and Stimulates Monascus Pigments and Monacolin K Production

Abstract: Applications of beneficial secondary metabolites produced by Monascus purpureus (M. purpureus) could be greatly limited for citrinin, a kidney toxin. The link of NaCl with cell growth and secondary metabolites in M. purpureus was analyzed with supplementations of different concentrations of NaCl in medium. The content of citrinin was reduced by 48.0% but the yellow, orange, red pigments and monacolin K productions were enhanced by 1.7, 1.4, 1.4 and 1.4 times, respectively, compared with those in the control us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Meanwhile, it induced the expression of ena1 to efflux some sodium ions to maintain intracellular Na + balance [Ferrigno et al, 1998; Ruiz et al, 2006; Lemos et al, 2018]. In addition, Zhen et al [2019] found that Na + could participate in the synthesis of secondary metabolites in M. purpureus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it induced the expression of ena1 to efflux some sodium ions to maintain intracellular Na + balance [Ferrigno et al, 1998; Ruiz et al, 2006; Lemos et al, 2018]. In addition, Zhen et al [2019] found that Na + could participate in the synthesis of secondary metabolites in M. purpureus .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was caused by the influence of ion concentration and membrane potential on electron distribution [Blank, 2005]. As one of the ions, NaCl could inhibit the biosynthesis of citrinin and contribute to the production of beneficial secondary metabolites ( Monascus pigments and monacolin K) [Zhen et al 2019]. We speculate that there was a certain relationship between the concentration of sodium ions and the change of secondary metabolites in M. purpureus caused by LF‐MF.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also discovered that the addition of different nitrogen sources such as ammonium, peptone, sodium nitrate, glutamic acid, monosodium glutamate, 6-furturylaminopurine, and tryptophan could enhance the yield of pigment, alter the hue of the fermentation liquid, and also improve light stability of the pigments of Monascus species [132,[140][141][142][143]. NaCl has been proved to be a very good enhancer that stimulates pigment production and inhibits citrinin production in M. purpureus without affecting the growth of the fungus [144]. A study on the effect of nutrients on pigment production of C. aeruginascens shows that high biomass but no pigment production was observed in media with high nutrient concentration, whereas low biomass and high pigmentation was observed in media with low nitrogen concentration [145].…”
Section: Optimization For Enhancement Of Pigment Productionmentioning
confidence: 99%
“…Further research is required to determine whether the metabolic regulation of environmental factors other than blue light also involves the participation of lncRNA AOANCR . In addition to light, other environmental factors, such as pH and temperature, can significantly affect the synthesis of citrinin [71,72]. LncRNA should also be considered as an important influencing factor in studies of the mechanism of the regulation of environmental factors to Monascus .…”
Section: Discussionmentioning
confidence: 99%